Pendekatan Integratif (Integrative Approach) dalam Pembelajaran Bahasa Arab Jarak Jauh di Masa Pandemi: An Integrative Approach in Distance Learning Arabic in a Pandemic Period - Muhammad Azhari (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2021)
Abstract With the COVID 19 pandemic which began in March 2020, it affected all community activities, incluiding activities in the educational environment, learning which was originally based directly with face to face, has now turned into online based learning or better known as distance learning (PJJ), distance learning is implemented so that student are protected from exposure to the covid 19 virus, but thus a new problem arises, namely how an educator can optimize learning well, especially in learning Arabic, one of the things that must be carried out by educators is to prepare an effective approach in distance learning Arabic. The integrative approach in learning Arabic is one of the curriculum implementation models that is applied to all levels of educatin, through this approach it is hoped that language learning, especially Arabic can make students easily acquire knowledge and master the four Arabic skills (istima’, kalam, qiraah, kitabah), completely and meaningfully. And one of the things that techers must do in learning Arabic usinh an integrative approach is to combine several skills in one lesson, and it can also be by integrating between two subjects. In practice this learning applies the principles of integrated learning, namely raising actual and authentic themes so that students remain enthusiastic in participating in learning. This study will describe the integrative approach applied distance learning Arabic, so that learning remains effective even though carried out online or distance learning.